Story Map of Kampung Jawa Tondano Visualization of Cultural Tourism Destinations - Anindya Puspita Putri; Selvana Treny Rosita Tewal; Grace Feibe E Suoth; Yemima Otuluwo (Technium Social Sciences Journal, 2024)
The use of story maps has been widely used to help overcome several problems, one of which is the use of story maps as a visualization medium for tourist destinations. Story map is an open-source platform developed by the Knight Lab at Northwestern University, this platform makes it possible to integrate historical and contemporary maps into interactive stories. Story maps are able to provide information related to tourist attractions online on a location basis. One of the cultural tourism destinations in Minahasa Regency is Kampung Jawa Tondano. This village was formed from the exile of Kiai Mojo and his followers as a result of the Java War, namely the conflict between Prince Diponegoro and the Dutch colonial government. Apart from providing information regarding Kampung Jawa Tondano, the use of story maps can be used as an initial step in developing tourist destinations in Minahasa Regency.